2020
DOI: 10.1093/rheumatology/keaa728
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for colchicine refractory familial Mediterranean fever: a cohort of 44 patients

Abstract: Objective FMF is an autoinflammatory disease of genetic origin. Colchicine is the mainstay of treatment for the prevention of attacks and long-term complications but 5–10% of FMF patients are resistant to colchicine therapy. The aim of our study was to investigate the real-life safety and efficacy of anakinra in a cohort of patients with colchicine-resistant FMF. Methods In this retrospective study, patients treated with anak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…13,14,17,[20][21][22]24 Anti-IL-1 therapies are highly beneficial in controlling inflammatory attacks in colchicine-resistant patients and may prevent ASBO. 9,10 There are no reports on the efficacy of anti-IL-1 therapy specifically in FMF patients whose disease is complicated with ASBO. However, Talerico et al 29 described a 65-year-old patient diagnosed with peritoneal mesothelioma due to repeated peritoneal inflammation of FMF.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,17,[20][21][22]24 Anti-IL-1 therapies are highly beneficial in controlling inflammatory attacks in colchicine-resistant patients and may prevent ASBO. 9,10 There are no reports on the efficacy of anti-IL-1 therapy specifically in FMF patients whose disease is complicated with ASBO. However, Talerico et al 29 described a 65-year-old patient diagnosed with peritoneal mesothelioma due to repeated peritoneal inflammation of FMF.…”
Section: Discussionmentioning
confidence: 99%
“…Marko et al showed that the Global Assessment Score assessed by the number of attacks per month, duration of attacks, and number of sites involved in the attacks decreased signi cantly from 6.6 (IQR 5.3-7.8) to 2 (IQR 0-4.2) in 44 colchicine-resistant patients with anakinra. Anakinra was reported to be bene cial for the majority of colchicine-resistant FMF patients [17]. Ben-Zvi et al found that among 25 patients with colchicine-resistant FMF, who were randomly assigned to groups that received anakinra consisting of 12 patients and placebo consisting of 13 patients, the number of monthly attacks was 1.7 ± 1.7 in the anakinra group and 3.5 ± 1.9 in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment period was much longer and the population much larger, than in the RCT, the results were comparable. Anakinra has been shown to reduce attack rate and severity, decrease the levels of inflammatory markers, and achieve improvement in composite measures, that included patient and physician global assessments such as FMF50 or global assessment score [ 139 , 140 , 141 , 142 , 143 ]. Usually, the toll of safety was minimal, mainly consisting of injection-site reactions, as discussed separately in Section 7.13 .…”
Section: Anakinra In Fmfmentioning
confidence: 99%
“…Shortly after the introduction of anakinra for the treatment of FMF, increasing evidence has begun to accumulate, suggesting that anakinra may favorably affect FMF-amyloidosis. Based on published data, it appears that anakinra may lead to stabilization [ 143 , 146 , 147 ], regression [ 139 , 142 , 147 , 148 ], and normalization of urinary protein levels, even in patients with nephrotic range proteinuria [ 139 , 149 ]. Pitifully, this beneficial effect is limited to early stages of amyloidosis, before significant renal failure develops [ 146 , 147 , 149 ].…”
Section: Anakinra In Fmfmentioning
confidence: 99%